Analyzing the Performance of a Solar-Assisted Grain Dryer - Parenden, Daniel; Sumbung, Frederik H.; Sahupala, Peter (Journal of Mechanical Engineering Science and Technology (JMEST), 2025)
This study evaluates the drying performance and energy efficiency of a solar-powered rice cabinet dryer equipped with two distinct airflow mechanisms: free convection (chimney-assisted) and forced convection (fan-assisted). Field experiments were conducted under tropical conditions in This study evaluates the drying performance and energy efficiency of a solar-powered rice cabinet dryer equipped with two distinct airflow mechanisms: free convection (chimney-assisted) and forced convection (fan-assisted). Field experiments were conducted under tropical conditions in Merauke, Indonesia, comparing drying efficiency, moisture reduction, and air mass flow across three rice grain loads: 1 kg, 3 kg, and 5 kg. The experimental design incorporated both thermal analysis and statistical evaluation (ANOVA and t-tests) to assess the effects of airflow method and grain weight on drying outcomes. Results indicate that the chimney system demonstrated more stable and efficient performance at lower grain weights (1–3 kg), with range efficiency of 32.07% - 37.5% compared to 28.26% - 32.67% using the fan-assisted method. Drying efficiency increases with grain load, reaching a maximum of 43.75% for chimney-assisted drying and 43.44% for fan-assisted drying at 5 kg. However, the fan-assisted system provided superior performance at higher loads due to improved heat and moisture transfer. Although the fan method yielded faster drying rates and more effective moisture reduction, it exhibited slightly greater variability. Despite limitations related to experimental scale and real-time solar radiation monitoring, the findings confirm that solar-powered cabinet dryers—especially those with adaptive airflow control—offer a cost-effective, energy-efficient, and scalable drying solution for smallholder rice producers. Future work should prioritize scaling up capacity, integrating hybrid energy sources, and automating temperature regulation to enhance system performance under fluctuating weather conditions